Caregivers' perception of women's dignity in the delivery room: A qualitative study. (February 2020) - Mohammadi, Fateme; Tabatabaei, Hadise sadate; Mozafari, Farzaneh; Gillespie, Mark
Introduction: Dignified care is one of the moral responsibilities of professional caregivers. However, in many cases the dignity of hospitalized patients, especially women in the delivery room, is not maintained. Dignity is an abstract concept and there has been no previous research exploring the dignity of pregnant women in the delivery room in Iran. Objectives: The objective of this study is to define and explain the concept of dignity for pregnant women in the delivery room from the perspectives of professional caregivers. Research design: This is qualitative research. The data were collected through in-depth semi-structured individual interviews. The conventional content analysis method was used to analyze the data. In qualitative content analysis, participant narrative is examined in-depth and sorted into categories and themes. Participants and research context: Potential participants who met the entrance criteria for this study were approached between July 2016 and February 2017. In all, 20 professional caregivers working in the delivery room setting within Iranian general hospitals were invited to participate in the study. The sampling was done through targeted sampling until saturation was achieved. Ethical considerations: The research ethics committee of the Shiraz University of Medical Sciences has approved the study's protocol and all commonly recognized ethical principles were followed throughout the study. Findings: The findings of this study were presented in three main themes, including "privacy, " "respecting patients' preferences, " and "comprehensive attention" and eight categories. Discussions and conclusion: Women in the delivery room need to be taken care of in an environment where healthcare staff promote the preservation of dignity through maintaining privacy, by providing attentive care and through ensuring that patient preferences regarding care and treatment are respected. In such an environment, the dignity of these women would be maintained and desirable outcomes achieved.